1998
DOI: 10.1097/00002030-199803000-00001
|View full text |Cite
|
Sign up to set email alerts
|

HIV p17 enhances lymphocyte proliferation and HIV-1 replication after binding to a human serum factor

Abstract: Characterization of the human factor(s) and identification of the interacting p17 epitope(s) will improve our understanding of the mechanisms used by HIV to efficiently replicate in our organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…Consequently, we have focused our efforts on studies of p17 and Env persistence in GCs of LNs. These findings may be relevant to lymphopathogenesis involving GC formation and B cell activation, because both these viral structural protein and glycoproteins interact with mononuclear cells and induce and͞or enhance a number of cytokines and chemokines that are critical in activation, recruitment, and cell proliferation (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, we have focused our efforts on studies of p17 and Env persistence in GCs of LNs. These findings may be relevant to lymphopathogenesis involving GC formation and B cell activation, because both these viral structural protein and glycoproteins interact with mononuclear cells and induce and͞or enhance a number of cytokines and chemokines that are critical in activation, recruitment, and cell proliferation (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that B cell stimulation and prolonged immune deficiency are main risk factors for non-Hodgkin's lymphoma (NHL) in people with AIDS (10). Given that at least the viral structural glycoproteins HIV-1gp120͞gp41 and the matrix protein HIV-1p17 possess a capacity to actively interact with cells of the immune system (23)(24)(25), the long-term presence in GCs of LNs points to the fact that at least one risk factor for NHL was not eliminated by antiretroviral therapy. Earlier observations showed that the serum-soluble CD23 level correlates with the subsequent development of AIDS-related NHL (55,56), and colocalization of CD23 expression in FDCs bounding the HIV-1 antigen-antibody complexes in GCs of LNs was also demonstrated (32 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations